Identification of a small RhoA GTPase inhibitor effective in fission yeast and human cells - Jun Morishita; Paul Nurse (Open Biology, 2023)
The Rho GTPase family proteins are key regulators of cytoskeletal dynamics. Deregulated activity of Rho GTPases is associated with cancers and neurodegenerative diseases, and their potential as drug targets has long been recognized. Using an economically effective drug screening workflow in fission yeast and human cells, we have identified a Rho GTPase inhibitor, O1. By a suppressor mutant screen in fission yeast, we find a point mutation in the rho1 gene that confers resistance to O1. Consistent with the idea that O1 is the direct inhibitor of Rho1, O1 reduced the cellular amount of activated, GTP-bound Rho1 in wild-type cells, but not in the O1-resistant mutant cells, in which the evolutionarily conserved Ala62 residue is mutated to Thr. Similarly, O1 inhibits activity of the human orthologue RhoA GTPase in tissue culture cells. Our studies illustrate the power of yeast phenotypic screens in the identification and characterization of drugs relevant to human cells and have identified a novel GTPase inhibitor for fission yeast and human cells.